2007
DOI: 10.1080/00207450500534050
|View full text |Cite
|
Sign up to set email alerts
|

SEX DIFFERENCES IN HUMAN LYMPHOCYTE Na,K-ATPase AS STUDIED BY LABELED OUABAIN BINDING

Abstract: Lymphocytes Na,K-ATPase is a plasma membrane enzyme that is up-regulated under lymphocytes activation. It is also studied as a model of brain cells Na,K-ATPase. Data about sex-related specificities of the enzyme are not available. The binding of tritium-labelled ouabain to lymphocyte plasma membrane Na,K-ATPase was studied in healthy volunteers of both sexes. The binding interactions were expressed in terms of K(D) and B(Max). The first parameter is related to the affinity of ouabain for the enzyme whereas the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
2
1
Order By: Relevance
“…A similar approach was followed to investigate if the variable monocytes sensitivity to PLTX could be affected by healthy volunteers' demographic factors. A previous study already demonstrated an increased affinity of the cardioactive glycoside ouabain for lymphocytes Na + /K + -ATPase in females as compared to males [29]. On the contrary, our results suggest that none of the demographic data (gender, age, and blood group) are related to the variable monocytes sensitivity to PLTX.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…A similar approach was followed to investigate if the variable monocytes sensitivity to PLTX could be affected by healthy volunteers' demographic factors. A previous study already demonstrated an increased affinity of the cardioactive glycoside ouabain for lymphocytes Na + /K + -ATPase in females as compared to males [29]. On the contrary, our results suggest that none of the demographic data (gender, age, and blood group) are related to the variable monocytes sensitivity to PLTX.…”
Section: Discussioncontrasting
confidence: 75%
“…Each of the α and the β subunits present more than one isoform, encoded by different genes, with different tissues expression pattern, as reported by the Model Organism Protein Expression Database (MOPED) [ 27 ]. Moreover, evidence demonstrates different expression patterns of Na + /K + -ATPase subunit isoforms between males and females [ 28 , 29 , 30 ] and it is well known that some isoforms of the α and β subunits own different affinities and sensitivities towards cardioactive glycosides [ 31 , 32 , 33 , 34 , 35 ]. Intriguingly, cardioactive glycosides, such as ouabain, are reported to inhibit PLTX in vitro effects [ 36 , 37 , 38 , 39 , 40 ], being able to modulate PLTX action on the Na + /K + -ATPase in a complex manner: Ouabain acts as a negative allosteric modulator against high PLTX concentrations and as a non-competitive antagonist against low PLTX concentrations [ 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…The sex difference may have been in part due to differences in the Na+/K+-ATPase responses (70). It has been shown in human peripheral blood lymphocytes that there is a sex difference in the expression and activity of this enzyme (71). In this study the investigators found differential expression of the Na+/K+ ATPase activity in the right and left side of the brain with the differential most pronounced in the female pups.…”
Section: Introductionmentioning
confidence: 99%